A General Approach To Study the Thermodynamics of Ligand Adsorption to Colloidal Surfaces Demonstrated by Means of Catechols Binding to Zinc Oxide Quantum Dots - Lin, Wei; Walter, Johannes; Burger, Alexandra; Maid, Harald; Hirsch, Andreas; Peukert, Wolfgang; Segets, Doris (Chemistry of Materials, 2015)
A general strategy to study the thermodynamics of ligand adsorption to colloidal surfaces was established. The versatility of our approach is demonstrated by means of catechols binding to ZnO quantum dots (QDs). First, isothermal titration calorimetry (ITC) was used to extract all relevant thermodynamic parameters, namely association constant, enthalpy, entropy, and free energy of ligand binding. Noteworthy, the determined ΔG of −20.3 ± 0.4 kJ mol–1 indicates a strong, reproducible, and exothermic interaction between the catechol anchor group and the oxide particle surface. To confirm the characterization of ligand binding by measuring the heat of adsorption, the free energy was cross-validated by mass-based adsorption isotherms. A combination of inductively coupled plasma optical emission spectroscopy (ICP-OES) and UV/vis spectroscopy was developed to quantitatively determine the mass of bound catechols with respect to the available particle surface. The association constant K was determined by a Langmuir fit to be 2618 M–1 which leads to ΔG = −19.50 kJ mol–1 according to ΔG = −RTln K. To close the mass balance, analytical ultracentrifugation (AUC) was applied to detect the amount of the free, unbound catechol in solution. Finally, Raman spectroscopy and nuclear magnetic resonance spectroscopy (NMR) were performed to quantify the amount of remaining acetate from particle synthesis and to distinguish bound (chemisorbed) and unbound (physisorbed) catechol. Our results reveal that approximately 65 wt % of acetate is replaced, and physisorbed catechol will not affect the amount of remaining acetate on the ZnO surface. Moreover, no pronounced chemical shift peak as it would be expected for free catechol is observed by NMR at all. This indicates a highly dynamic adsorption–desorption equilibrium between the free and the physisorbed state of catechol on the particle surface. Our concept of combined analytics is seen to be a generally applicable strategy for particle-ligand interfacial studies. It gives detailed insight into thermodynamics, binding states, and ligand composition and is thus considered as an important step toward tailored colloidal surface properties.